Perceived color of undoped electrospun polyacrylonitrile nanofibers. Issue 17 (14th June 2017) - Whitford, Jonathan; Shinde, Manish; Hunt, Brandon; Miller, Sandy; Kostogorova‐Beller, Yulia
ABSTRACT: This work reveals influence of electrospinning of polyacrylonitrile– N, N ‐dimethylformamide solution of different concentrations on nanofiber web color parameters, molecular structure, and heat stability. It is found that fiber diameters depend on concentration through the power law relationship; however, the medium concentration‐based web is characterized by a green–yellow hue, representative of the chromophore color; while, the solvent‐rich and solvent‐poor solution‐based webs give rise to Stokes shifts and ultraviolet‐blue emission bands, attributed to fluorescence. The chromophore structure, present in the neat powder, undergoes changes as a result of electrospinning reflected by the enamine‐to‐ketonitrile conversion and the fraction of CN conjugation. Blue‐shifting of the CN conjugation is indicative of a reduction of the π‐electron system, which is coincident with the decreased color saturation value but observed only in the nanofibers prepared from the medium concentration solution. A decrease in the glass transition and an increase in cyclization temperatures also support these findings. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 1278–1285 Abstract : This work reveals influence of electrospinning processing of polyacrylonitrile powder on resulting nanofiber diameters, their perceived color, microstructural changes, and heat stability. It is found that the diameters depend on the solution concentration through the power law relationship. However, the medium‐concentration nanofibers are characterized by a green‐yellow hue, representative of the chromophore color; in contrast, the solvent rich and poor solution‐based webs give rise to Stokes shifts and ultraviolet‐blue emission bands attributed to fluorescence.